Formulation and Evaluation of Sustained Release Matrix Tablets of Glipizide: Sustained release matrix tablets of glipizide - P.R. Radhika; T.K. Pal; T. Sivakumar (Iranian Journal of Pharmaceutical Sciences, 2009)
The purpose of this study was to develop a new monolithic matrix tablet to completely deliver glipizide in a zero order manner over a sustained period. Two approaches were examined using drug in a formulation that contain polymer like hydroxylpropyl methyl-cellulose K 100 (HPMCK) and Eudragit L100. The granules were prepared by wet granulation method and thereby formulated as F-1, F-2. F-3 and F-4 by using the above bring up polymers with other ingredients. The granules of different formulations were evaluated for angle of repose, loose bulk density and tapped density, compressibility index, total porosity,and drug content. The angle of repose and compressibility index (%) ranged from 25.0±0.8to 28.0±1.1 and 12.92±0.02 to 13.08±0.03, respectively. The results of angle of repose (<30)indicate good flow properties of the granules. This was further supported by lower com-pressibility index values. The granules showed satisfactory flow properties, compressibility and drug content. All of the formulations showed uniform thickness (C.V< 0.5%), uniform weight with little significance difference were observed with varying formulation composition.In the weight variation test, the pharmacopoeial limit for the percentage of deviation for tablets of more than 130 mg to 324 mg is 7.5 % difference. Technological characterizations (thickness, diameter, weight variation test, drug content, hardness, and friability) were conceded with the formulated matrix tablet and in vitrodrug release was measured by meansof dissolution apparatus. Of the various formulation distinguished, out of which, theformulation (F3) were preferred to be full of 30 mg of HPMCK and 35 mg of Eudragit L100was subjected to stability were accomplished studies for three months at 4 °C. The roomtemperature (25 °C) and (45 °C) with relative humidity 75±5% were maintained and itsstability with respect to release pattern. The kinetic release treatment showed that therelease of drug follows zero order kinetic (r2= 0. 9959), Koresmeyer equation gave valueof r2= 0.9853 which was close to one indicating that the drug was released by zero orderkinetic. According to Koresmeyer equation, the formulation F-1, F-2, and F-4 showed the regression values of 0.9823, 0.9785, and 0.9742, respectively. The identical plot for (logcumulative percentage drug release vs time) for Koresmeyer-Peppas equation indicated agood linearity for the commercially available sustained release tablet and formulation F-3 with regression values of 0.9619 and 0.9959, respectively. Scanning electron microscope confirmed both diffusion and erosion mechanism for the optimized batch of matrix tabletF-3. Results suggest that the formulated tablet F-3 of glipizide could perform therapeuti-cally better than the reachable marketed drug leading to improve better efficacy.